Systematic review of adverse events of buprenorphine patch versus fentanyl patch in patients with chronic moderate-to-severe pain. (July 2012) - Wolff, Robert F; Reid, Kim; di Nisio, Marcello; Aune, Dagfinn; Truyers, Carla; Hernandez, Adrian V; Misso, Kate; Riemsma, Rob; Kleijnen, Jos
SUMMARY  This systematic review compares convenience of administration, adverse events and tolerability of buprenorphine patch with fentanyl patch in patients with chronic pain. Methods of quantitative and qualitative research were combined. Seventeen databases were searched up to December 2010. A total of 49 unique trials (56 publications) were included. Patients regarded the use of patches, both transdermal buprenorphine and fentanyl, as easy and convenient. Compared with buprenorphine patch, fentanyl can cause more cases of constipation and could lead to a higher number of serious adverse events. There were no differences between buprenorphine patch and fentanyl patch regarding dizziness, somnolence, nausea and treatment discontinuation. Overall, transdermal administration of buprenorphine and fentanyl can be seen as an alternative pathway for delivering these drugs. Use of transdermal buprenorphine might be favorable in certain groups of patients, such as renally impaired, elderly and immunosuppressed patients.